The Impact of War on the Mental Health of Youth: The Role of Resilience and Psychological Interventions - Sodolevska, Valeriia (Psychosomatic Medicine and General Practice, 2024)
Relevance. In the context of war, it is crucial to investigate psychological defense mechanisms and resilience, which enable adaptation to extreme conditions. Resilience is a key factor in preventing long-term negative mental health consequences, helping young people better cope with stressful situations and reducing the risk of developing psychopathology. Formulating effective methods of psychological support and intervention is an important aspect of psychosocial rehabilitation aimed at improving the quality of life for young people affected by military conflicts. Objective. To analyze the effectiveness of psychological interventions in enhancing resilience as a protective factor against the impact of war on the mental health of young people in Ukraine. Methods. The study design was a parallel randomized, non-blinded controlled trial with two groups. The study involved 50 participants aged 18 to 35 years with adaptation disorders caused by military events in Ukraine. All participants were informed about the purpose and conditions of the study, and their participation adhered to ethical and deontological norms. The study utilized validated psychodiagnostic methods to assess participants’ mental health: the PHQ-9 scale to assess the level of depression, the GAD-7 scale to measure anxiety, and the CD-RISC-10 scale to assess resilience. Results. The study results showed significant improvements in the mental health of participants in the intervention group after the intervention. The PHQ-9 and GAD-7 scales showed a significant reduction in depression and anxiety levels (p < 0.001). Resilience levels, measured by the CD-RISC-10 scale, reached a high level in 96% of participants (p < 0.001). Changes in the control group were minimal. Conclusions. The results of this pilot study showed significant improvements in the mental health of the intervention group participants after 35 days of psychological intervention, particularly in reducing depression and anxiety levels, as well as increasing resilience (p < 0.001). These results underscore the effectiveness of psychological interventions and their potential for scaling up to a larger number of participants. It is important to expand the study to other categories of young people affected by the war to assess the long-term effectiveness of the interventions and to support the development of adaptive resources in crisis situations.